Human Resource Readiness for Big Data-Based Halal Tourism - Meriandini, Nanik Dela; Ardyansyah, Farid; Nasik, Khoirun (Indonesian Journal of Law and Economics Review, 2025)
General Background: Halal tourism has emerged as a rapidly growing global industry that integrates Islamic values with modern tourism practices. In the digital era, the use of big data technology has become essential to enhance competitiveness and optimize tourism management. Specific Background: Madura, known for its strong Islamic culture and diverse natural attractions, holds great potential for halal tourism development. However, effective implementation depends on the readiness of human resources (HR) to utilize big data strategically. Knowledge Gap: Despite increasing research on halal tourism, few studies have analyzed HR readiness in adopting big data for halal tourism management, particularly in socially and religiously distinctive regions like Madura. Aims: This study aims to analyze the readiness of Madura’s HR in managing halal tourism through big data utilization using a qualitative descriptive method and SWOT analysis with IFAS–EFAS matrices. Results: Findings show that Madura’s HR demonstrates strong conceptual and social readiness, supported by government policies and youth adaptability, yet faces challenges in digital literacy and infrastructure. Novelty: The integration of HR readiness assessment with big data indicators (5V) and SWOT analysis provides a unique framework for digital-based halal tourism evaluation. Implications: The study contributes to policy formulation and HR capacity-building strategies to strengthen Madura’s competitiveness in global halal tourism. Highlights:   Highlights Madura’s HR adaptability in managing halal tourism through big data. Identifies digital literacy and infrastructure gaps as key development challenges. Proposes strategic HR capacity-building for global halal tourism competitiveness. Keywords: Human Resource Readiness, Halal Tourism, Big Data, Digital Literacy